PEMBUATAN EDIBLE FILM DARI TEPUNG KORO BENGUK (Mucuna pruriens C. utillis L. DC) - Bambang Kunarto (JURNAL LITBANG PROVINSI JAWA TENGAH, 2006)
Edible film was film pack that made from edible substance (carbohidrat, hidrofobic substance, fat, protein) to increase shelflife food product in storage. Edible film could be developed as barrier moisture, gases and solute movement. This research was conducted to make edible film from velvet bean flour (Mucuna pruriens f. utilis L. DC). Data were collected from experiment and analized by the analysis of variance with completely randomized design with 3 x 3 arrangement. The first factor is velvet bean consentration (5%, I 0%, 15% w/v). The second factor is pH (pH 3, pH 6, pH 9). The result of research that consentration of velvet bean had significant effect on thickness, elongation, tensile strength and water vapor transmission rate,While pH had significant on elongation, tensile strength and water vapor transmission rate, but did not have significant on thickness. The combination treatment velvet bean flour in 15% consentration and pH 9 resulted the lowest water vapor transmission rate ( 13,06 g/m2hr), the higest tensile strength (4,61 Mpa), thickness 0, 154 mm and elogation 9 ,22%.